2004
DOI: 10.1111/j.1365-294x.2004.02336.x
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite and mitochondrial DNA analyses of Atlantic bluefin tuna (Thunnus thynnus thynnus) population structure in the Mediterranean Sea

Abstract: Genetic variation was surveyed at nine microsatellite loci and the mitochondrial control region (868 bp) to test for the presence of genetic stock structure in young-of-the-year Atlantic bluefin tuna (Thunnus thynnus thynnus) from the Mediterranean Sea. Bluefin tuna were sampled over a period of 5 years from the Balearic and Tyrrhenian seas in the western basin of the Mediterranean Sea, and from the southern Ionian Sea in the eastern basin of the Mediterranean Sea. Analyses of multilocus microsatellite genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

21
122
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 53 publications
21
122
1
Order By: Relevance
“…The first was whether there is solid genetic evidence for population structuring in the Mediterranean Bluefin tuna. Our data show that there are statistically significant differences among population samples, confirming and strengthening previous results obtained with the same approach on a few samples (12,24). Despite the documented individual tendency to disperse in various life stages, different samples of ABFT show genetic differences over space and time, both at the fine and large scales of variation.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The first was whether there is solid genetic evidence for population structuring in the Mediterranean Bluefin tuna. Our data show that there are statistically significant differences among population samples, confirming and strengthening previous results obtained with the same approach on a few samples (12,24). Despite the documented individual tendency to disperse in various life stages, different samples of ABFT show genetic differences over space and time, both at the fine and large scales of variation.…”
Section: Discussionsupporting
confidence: 81%
“…Size-dependent movements and spawning in different areas and periods have been documented (15,(21)(22)(23). Genetic variation among three geographical samples suggested that at least two subpopulations inhabit and persist over short time periods (3 years) in the western and eastern Mediterranean Sea, yielding Wright's genetic variance (F ST ) values within the Mediterranean Sea between 0.0007 and 0.0087 (12,24). In this study, we started from a more thorough sampling of Mediterranean ABFTs in space and time.…”
mentioning
confidence: 99%
“…Further speculation regarding the origin of the subtle differences in otolith shape that were observed within the Mediterranean and East Atlantic would be beyond the limitations of currently available data. However, the results indicate that variation in otolith shape could potentially be used to distinguish between Atlantic bluefin spawning in different areas of the Mediterranean and to resolve the structuring that has been observed here (Carlsson et al 2004;Riccioni et al 2010). This would require the collection of baseline samples from putative spawning areas during the spawning season, which were not available for the present study.…”
Section: Discussionmentioning
confidence: 80%
“…Analyses of DNA microsatellites (Carlsson et al 2007), mitochondrial DNA (Boustany et al 2008) and single nucleotide polymorphisms (Albaina et al 2013) all show significant genetic divergence of the two populations. In addition, there is evidence of genetic heterogeneity within the Mediterranean, and the existence of separate spawning populations in the western and eastern Mediterranean has been proposed (Carlsson et al 2004;Riccioni et al 2010). The occurrence of mature adult Atlantic bluefin tuna in areas other than the main spawning grounds during the spawning season may also be indicative of a more complex structure than the currently accepted two-stock model (Galuardi et al 2010).…”
Section: Introductionmentioning
confidence: 97%
“…Recent studies in coastal habitats, however, have revealed that the larvae of many coral reef fish species actually settle much closer to their natal reefs than previously thought (Almany et al, 2007;Jones et al, 1999;Kingsford et al, 2002;, Swearer et al, 1999Taylor & Hellberg, 2003). Similarly, population structure has been found in pelagic species such as cod (Bentzen et al, 1996;Ruzzante et al, 2000) and tuna (Block et al, 2005;Carlsson et al, 2004). The existence of patchy marine populations, especially if the patches are not connected by migration or dispersal, has enormous implications for biodiversity conservation and management.…”
Section: Introductionmentioning
confidence: 91%